Retroviral Vector-mediated Gene Therapy to Mucopolysaccharidosis I Mice Improves Sensorimotor Impairments and Other Behavior Deficits - Baldo, Guilherme (2012)
Mucopolysaccharidosis I (MPS I) is a lysosomal storage disease due to α-L-iduronidase (IDUA) deficiency that results in the accumulation of glycosaminoglycans (GAG). Systemic gene therapy to MPS I mice can reduce lysosomal storage in the brain, but few data are available regarding the effect upon behavioral function. Here, we investigated the effect of gene therapy with a long-terminal repeat (LTR)-intact retroviral vector or a self-inactivating (SIN) vector on behavioral function in MPS I mice. The LTR vector was injected intravenously to 6 week-old MPS I mice, while the SIN vector was given to neonatal or 6 week-old mice. Adult-LTR, Neonatal-SIN, and Adult-SIN-treated mice achieved serum IDUA activity that was 235±20 (84-fold normal), 127±10, and 71±7 units/ml, respectively. All groups had reduction in histochemical evidence of lysosomal storage in the brain, with the Adult-LTR group showing the best response, while Adult-LTR mice had reductions in lysosomal storage in the cristae of the vestibular system. Behavioral evaluation was performed at 8 months. Untreated MPS I mice had a markedly reduced ability to hold onto an inverted screen or climb down a pole. LTR vector-treated mice had marked improvements on both of these tests, while Neonatal-SIN mice had improvements in the pole test. We conclude that both vectors can reduce brain disease in MPS I mice, with the LTR vector achieving higher serum IDUA levels and better correction. Vestibular abnormalities may contribute to mobility problems in patients with MPS I, and gene therapy may reduce symptoms.